Spillovers of community-based health interventions on consumption smoothing - Emla Fitzsimons; Bansi Malde; Marcos Vera-Hernández (University of Kent, School of Economics, 2016)
Community-based interventions, particularly group-based ones, are considered to be a cost-effective way of delivering interventions in low-income settings. However, design features of these programs could also influence dimensions of household and community behaviour beyond those targeted by the intervention. This paper studies spillover effects of a participatory community health intervention in rural Malawi, implemented through a cluster randomised control trial, on an outcome not directly targeted by the intervention: household consumption smoothing after crop losses. We find that while crop losses reduce consumption growth in the absence of the intervention, households in treated areas are able to compensate for this loss and perfectly insure their consumption. Asset decumulation also falls in treated areas. We provide suggestive evidence that these effects are driven by increased social interactions, which could have alleviated contracting frictions; and rule out that they are driven by improved health or reductions in the incidence of crop losses.
Keywords: E21; G22; O12; O13; 330; participatory community interventions; spillovers; consumption smoothing; Sub-Saharan Africa